An analysis Code Switching Used by The Students and The Teacher at Senior High School in Al Zahrah Boarding School: An analysis Code Switching Used by The Students and The Teacher at Senior High School in Al Zahrah Boarding School - Ullya Zainura (Journal of English Education and Social Science, 2022)
This research aimed to analyse code switching used by the students and the teacher in foreign language classroom. In detail, the researcher interest in finding the teacher’s language used, and the students’ language used. Then, it also observed the reason why they do code switching. This research was designed descriptively. The subject of this research was English teacher and the students at MAS Al Zahrah. The data of this research was the English teacher’ and the students’ utterances which contain code-switching. The instrument used was an audio-video recorder which recorded the classroom conversation. The results showed that the code mostly used by the English teachers and the students was Bahasa Indonesia. Then, the other dominant codes were English, switching English – Bahasa Indonesia, and switching Bahasa Indonesia – English. The finding of this research was the teacher and the students did code-switch more than target language in teaching learning process. They believe that code switching is an effective way in learning.